Chemical constituents of the extract Algerian Reutera lutea (Desf.) Maire, (Apiaceae) - E, Makhloufi; S, Akkal; K, Medjroubi; A, Elomri; H, Laouer; P, Verité; E, Seguin (Pharmacognosy Communications)
Phytochemical analysis of the aerial parts of Reutera lutea (Apiaceae), resulted in the isolation of two flavonoid C-glucosides and isocoumarine. The structures of the compounds were established as Isoorientin (1), Isoorientin 6”-O-acetate (2) and 3,4-dihydro-6, 8-dihydroxy-3-methylisocoumarin (3). The structures of all compounds were elucidated by spectroscopic methods, including (1D and 2D NMR, UV, MS).
Keywords: Apiaceae; Reutera lutea; flavonoid; C-glucosides; Isocoumarin